2011
DOI: 10.1073/pnas.1100892108
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex and striatum mediate the influence of social comparison on the decision process

Abstract: We compared private and social decision making to investigate the neural underpinnings of the effect of social comparison on risky choices. We measured brain activity using functional MRI while participants chose between two lotteries: in the private condition, they observed the outcome of the unchosen lottery, and in the social condition, the outcome of the lottery chosen by another person. The striatum, a reward-related brain structure, showed higher activity when participants won more than their counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(157 citation statements)
references
References 42 publications
9
145
2
Order By: Relevance
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 84%
“…Building on extensive behavioral studies in the domain of social psychology, the past decade has witnessed an increased interest in unveiling the neural signatures of social comparison [Bault et al, 2011;Beer and Hughes, 2010;Fliessbach et al, 2007;Hughes and Beer, 2013;Luo et al, 2015;Wu et al, 2012]. To have participants compare themselves to others, these studies usually employed experimental paradigms in which participants are exposed to both their own and another person's/group's performance or outcomes [Boksem et al, 2011;Fliessbach et al, 2007;Qiu et al, 2010;Zhen et al, 2016;Zink et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Here, BOLD activity in a given participant's ventral striatum co-varied with the payoff to this player when the other player did not receive any money, but it reflected relative payoff (compared with the other's gain) when both players received money 77 . Another study found that this relative reward coding did not occur if the observed outcome was not actually paid to another person 78 , underlining that the modulation of ventral striatum activity was due to 'social comparison' of one's own outcome to that of others (rather than merely to the numerical discrepancy between two outcomes).…”
Section: Neural Valuation Of Normative Social Principlesmentioning
confidence: 99%
“…In the present study we did not observe, however, activations in the ventral striatum (VS) for downward comparisons, although such activations have been reported on several occasions before (Bault et al, 2011;Dohmen, Falk, Fliessbach, Sunde, & Weber, 2011;Du et al, 2013;Dvash, Gilam, Ben-Ze'ev, Hendler, & Shamay-Tsoory, 2010;Fliessbach et al, 2007Fliessbach et al, , 2012Grygolec, Coricelli, & Rustichini, 2012;Kang, Lee, Choi, & Kim, 2013;Lindner et al, 2015; for a review see . The VS constitutes one of the main structures of the reward system.…”
Section: Discussionmentioning
confidence: 41%
“…At the brain level, we intended to test whether low distance self-other comparisons engage self-related regions, i.e., the MPFC, the AI and the ACC, to a greater extent than high distance comparisons. Finally, one characteristic of self-other comparisons is that the direction of the comparison is crucial: Comparisons with upward standards are likely to elicit negative emotions (Beer & Hughes, 2010;Lindner et al, 2015), whereas downward comparisons may rather be rewarding (Bault, Joffily, Rustichini, & Coricelli, 2011;Fliessbach et al, 2007). Thus, in the present study, we modelled in the parametric design the direction of the comparison (upward vs downward) in addition to the comparison targets (self-other vs familiar-other) and the perceived distance between the two comparison targets (high vs low distance) to produce a 2 × 2 × 2 design.…”
Section: Introductionmentioning
confidence: 99%